MANAGEMENT PROGRAMS TO CONTROL Conyza spp. IN PRE-SOYBEAN SOWING APPLICATIONS - Zobiole, L. H. S.; Krenchinski, F. H. [UNESP]; Pereira, G. R.; Rampazzo, P. E.; Rubin, R. S.; Lucio, F. R. (Univ Federal Vicosa, 2018)
The goal of this study was to compare the efficacy of different weed management through a burndown application followed by sequential applications of herbicides to control Conyza spp. Thus, four field experiments were conducted, two in the western region of Parana state (E1 and E2), one in Jatai, Goias state (E3) and another one in Ibiruba, Rio Grande do Sul state (E4). Conyza spp. in this area had a height ranging between 25 and 60 cm. Treatments were arranged in a randomized block design with four replications. The primary herbicide treatments were 2,4-D + glyphosate + diclosulam, chlorimuron-ethyl + glyphosate + 2,4-D, and four doses of diclosulam + halauxifen-methyl + glyphosate. These treatments were applied singly or in sequential applications, made 10 days before the application of ammonium glufosinate, paraquat or saflufenacil. In all experiments, results showed efficient (90%) control of treatments containing diclosulam + halauxifen-methyl in combination with glyphosate on day 35 DAA, regardless of sequential applications. Applications of 2,4-D + glyphosate + diclosulam or chlorimuron-ethyl + glyphosate + 2,4-D were not effective against Conyza spp. at E1 and E2 locations, possibly due to the greater weed size (50 to 60 cm) at these sites. However, the same treatments were effective at E3 and E4 locations, where weeds were smaller. Diclosulam + halauxifen-methyl + glyphosate associated with ammonium glufosinate, paraquat or saflufenacil in sequential applications, proved to be an important tool to manage Conyza spp. at different growth stages.
Keywords: horseweed control; herbicide; sequential application; weed